ANALISIS SATUA BALI I LUBDAKA DALAM MENANAMKAN NILAI KARAKTER DAN KEARIFAN LOKAL PADA ANAK SD - Ida Bagus Gede Surya Abadi; Chindytia; Putu Yuni Ari Surya; Ni Luh Putu Purnama Dewi; Anak Agung Sinta Laksmiyanti Pemayun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to examine the character values and local wisdom contained in the Balinese folktale I Lubdaka and its relevance in elementary school learning. The method used is a literature study by utilizing various written sources such as books, journals, and the text of I Lubdaka. The data were analyzed by identifying narratives and excerpts that reflect character values. The results show that the story contains religious values, self-awareness, responsibility, discipline and perseverance, as well as life balance in the concept of Tri Hita Karana. These values can be used as learning media to help students understand and apply moral values in their daily lives. In addition, the use of Balinese folktales in learning can increase students’ interest and support the preservation of local culture. Therefore, I Lubdaka can be used as an alternative medium for character education in elementary schools.